Spacetimes matter : a collection of mapping methodologies / edited by Jamie-Scott Baxter, Anna Juliane Heinrich, Séverine Marguin, Vivien Sommer. - Baxter, Jamie-Scott; Heinrich, Anna Juliane; Marguin, Séverine; Sommer, Vivien (Jovis, 2025)
How can mapping capture the dynamic entanglements of space and time in a rapidly changing world? 'Spacetimes Matter' is an invitation to rethink mapping as a critical tool for understanding multiple spacetimes - and how they come to matter.